2022
DOI: 10.1029/2021jd035985
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Changes in Eastern U.S. Pollution Events in a Warming World

Abstract: Risk assessments of air pollution impacts on human health and ecosystems would ideally consider a broad set of climate and emission scenarios, as well as natural internal climate variability. We analyze initial condition chemistry-climate ensembles to gauge the significance of greenhouse-gas-induced air pollution changes relative to internal climate variability, and consider response differences in two models. To quantify the effects of climate change on the frequency and duration of summertime regional-scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 94 publications
(165 reference statements)
0
26
0
2
Order By: Relevance
“…In contrast, internal variability in climate-induced changes to PM 2.5 remains consistent across climate sensitivities explored. While several studies have reported climate penalty on the upper tails of projected future air pollution distributions [5,13,23,48,54], further work investigating high pollution events can shed additional light on the interconnections different of climate in simulations of air quality impacts.…”
Section: Influence Of Climate Sensitivity On Projected Air Quality Im...mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, internal variability in climate-induced changes to PM 2.5 remains consistent across climate sensitivities explored. While several studies have reported climate penalty on the upper tails of projected future air pollution distributions [5,13,23,48,54], further work investigating high pollution events can shed additional light on the interconnections different of climate in simulations of air quality impacts.…”
Section: Influence Of Climate Sensitivity On Projected Air Quality Im...mentioning
confidence: 99%
“…However, sub-decadal simulations have proven insufficient to filter out the noise of internal variability in projections of climate impacts on O 3 and PM 2.5 and the associated health impacts [25,26,52,53]. Although large ensembles offer an effective approach to capture internal variability in climate projections [19], few studies have used initial condition ensembles to simulate climate change impacts on air quality [23,50,51,53]. Here, we rely on multiple model initializations and 30 year periods to represent a range of internal variability and weigh its influence on projected climate change impacts on pollutant concentrations.…”
Section: Influence Of Internal Variability On Projected Air Quality I...mentioning
confidence: 99%
See 2 more Smart Citations
“…Another major application of initialized ensembles is to determine a robust anthropogenic climate change signal, and hence inform approaches in the field of the detection and attribution of anthropogenic climate change. At its simplest, the anthropogenic climate change “signal” is represented by the ensemble mean whilst the internal climate variability “noise” emanates from the initialized ensemble range (Fiore et al., 2022).…”
Section: The Main Types Of Uncertaintymentioning
confidence: 99%